2012
DOI: 10.4103/2045-8932.105041
|View full text |Cite
|
Sign up to set email alerts
|

Subdural Hematomas in Pulmonary Arterial Hypertension Patients Treated with Protacyclin Analogs

Abstract: Prostacyclin analogs therapy has been associated with development of thrombocytopenia. Little is known whether this treatment increases the risk of intracranial hemorrhage in pulmonary artery hypertension (PAH) patients. We queried the Cleveland Clinic billing database to identify cases of nontraumatic sudural hematoma (SDH) in patients with PAH. We identified those individuals who were receiving prostacyclin analogs therapy at the time of the neurological event and assessed whether these patients were also ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In line with previous studies, we showed that prostacyclin analogues inhibit platelet reactivity and decrease platelet EV release. Additionally, we showed that impaired platelet function is associated with impaired thrombus formation, explaining the pathophysiological mechanisms underlying increased risk of bleeding in patients treated with prostacyclin analogues [ 40 , 41 ]. We observed that two patients who did not achieve clotting in the whole blood perfusion systems subsequently experienced bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, we showed that prostacyclin analogues inhibit platelet reactivity and decrease platelet EV release. Additionally, we showed that impaired platelet function is associated with impaired thrombus formation, explaining the pathophysiological mechanisms underlying increased risk of bleeding in patients treated with prostacyclin analogues [ 40 , 41 ]. We observed that two patients who did not achieve clotting in the whole blood perfusion systems subsequently experienced bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient's platelet count on presentation of her SDH was 245 x 10*9/L, making thrombocytopenia an unlikely cause for hemorrhage. While rare, there have been several cases of non-traumatic SDH described in PAH patients, mainly occurring in patients receiving epoprostenol while on anticoagulation with vitamin K antagonists independent of INR value [6][7][8]. Interestingly, CTD-PAH patients in the Henkens et al study were also noted to have a significantly higher rate of major bleeding than other PAH sub-groups.…”
Section: Discussionmentioning
confidence: 94%
“…Louis et al reported that one patient had a low normal platelet count, a condition in which the platelet levels decreased after continuous intravenous treprostinil administration for approximately 7 months. [ 17 ] Wang and Chen also reported a case of treprostinil-induced thrombocytopenia, for which the platelet counts were directly related to the rate of intravenous treprostinil administration. [ 18 ] We have not yet seen studies about the pathogenesis of thrombocytopenia caused by treprostinil treatment.…”
Section: Discussionmentioning
confidence: 99%